Evaluation of quality of life in a HIV carriers’ group - Souza, Fernanda G.; Kulkamp, Irene Clemes; Galato, Dayani (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: nowadays the quality life had its concepts enlarged especially because of the chronic diseases. The World Health Organization organized a universal quality of life instrument, the WHOQOL-bref, this instrument was developed by WHOQOL-lOO. Objetives: the objective was to evaluate the HIV carriers’ quality of life group. Methods: it is a transversal study based on interview technique using WHOQOL-bref instrument. Forty HIV carriers’ were interviewed. Results: the quality of life average was of 65.0%. There is significance between QV2 and the group presents adverse reactions by antiretrovirals (0.0391), the regress opportunistic diseases group (0.0272) and the actual opportunistic diseases (0.0086). Conclusion: it was verified that the adverse reactions to the medicine and to the opportunistic diseases have influenced negatively in the quality of life, this situation can be different when existing the rational use drugs and the following of patient by health equip.